A study comparing VVI and DDI pacing in elderly patients with carotid sinus syndrome. - McIntosh, S. J. (1997)
OBJECTIVE: To determine whether single chamber ventricular demand (VVI) pacing is adequate for elderly patients with carotid sinus syndrome. DESIGN: Prospective double blind randomised cross over study. SETTING: Tertiary referral centre. PATIENTS: 30 consecutive patients aged over 60 years with carotid sinus syndrome referred for cardiac pacing. INTERVENTION: Patients underwent dual chamber pacemaker implantation and were then randomised to two three-month periods of VVI and DDI pacing. MAIN OUTCOME MEASURES: Responses to cardiovascular tests (vasodepression during carotid sinus massage, pacemaker effect, postural blood pressure measurements, and response to head up tilt), and symptoms. RESULTS: 11 patients developed profound hypotension during upright carotid sinus massage while pacing VVI compared with only two while pacing DDI. The upright pacemaker effect was greater in VVI (VVI, -31 (SD 19) mm Hg v DDI, -4 (12) mm Hg; P < 0.001). Postural blood pressure measurements and responses to head up tilt did not vary. Eleven patients were unable to tolerate VVI pacing and had to be withdrawn early from this limb of the study (group A). Fourteen of the remainder completed diary cards and did not express a preference (group B). No patient preferred VVI. Group A patients were older (group A, 78 (6) years v group B, 70 (9) years; P < 0.05), were more likely to be female (group A, 73% v group B, 14%; P < 0.01), and were more likely to have orthostatic hypotension while pacing DDI (group A, 46% v group B, 0%; P < 0.01). Group A and B patients could not be differentiated by other prepacing clinical or haemodynamic variables. CONCLUSIONS: Elderly patients with carotid sinus syndrome are likely to develop symptomatic hypotension following VVI pacing. The optimum pacing mode for individual patients cannot be predicted by simple cardiovascular tests before pacing.